Innovation Digital Marketing In Increase Interest Buy Martabak Terang Bulan Arum Consumer - Septria, Vira; Albant Triswandi, Salsalliah; Naila Nasution, Muthia; Yuliana, Yayuk (International Journal of Science, Technology & Management, 2025)
This study aims to analyze the impact of digital marketing innovation on increasing consumer purchasing interest in Martabak Terang Bulan Arum products. In the digital era, the use of technology-based marketing strategies is one of the keys to winning competition in the culinary market. The research method used is a quantitative approach with data collection techniques through surveys, interviews, and social media analysis. The results of the study show that the application of digital marketing innovation, such as the use of social media, creative content creation, and collaboration with influencers, significantly increases consumer purchasing interest. In addition, factors of service personalization and direct interaction with consumers also contribute positively to customer loyalty. This study provides recommendations for culinary business actors to further utilize digital platforms as an effective and sustainable marketing tool.